(untitled) (Doctor Virtualis, 2011)
Può il brusio di una voce essere anche il luogo di una lingua? E vale questa topica anche nel caso in cui la voce sia quella di uno strumento musicale? Queste domande sono alla base della indagine sulla tecnica compositiva della tintinnabulatio, inventata e sperimentata dal musicista estone Arvo Pärt (Paide, 1935). I tintinnabuli consistono di due elementi apparentemente contraddittori: la sonorità pastosa dello zvod (le campane della liturgia ortodossa russa) e l’armonia della triade perfetta. Muovendo da un disco ricevuto in dono e dalla interpretazione in parte inedita di un passo di san Paolo, l’autore cerca di individuare il punto di articolazione dei tintinnabuli, quella “grana” dove – come disse una volta Roland Barthes – una lingua incontra una voce. Il problema musicale sottende le interminabili discussioni trinitarie dell’Oriente cristiano – qui per sfortuna solo accennate – e si manifesta nella figura dell’iconografo medievale Andrej Rublëv, cui il regista russo Tarkovskij ha dedicato, nel 1966, un denso e ispiratissimo film. Could the rustling of a voice be also the place of a language? And does it happen all the same, when the voice at issue is that of an instrumental body? Such questions are the basic ones for any inquiry into Arvo Pärt’s tintinnabuli—the technique invented and experienced by the famous Esthonian composer ( born in Paide, the 1935). It consists of two seemingly conflicting elements: the doughy resonance of the zvot (i.e. the Russian liturgical set of bells); and the harmony of the perfect triad. The present paper moves from the personal memory of listening Pärt’s elegy Silouans Song. The delicate instrumental piece is said to conceal a prosodical calque of the voice of the famous staretz Silouan the Athonite (1866-1938). Silouan’s song —to use Barthes’ words—is the very place where “a language does meet a voice”. Some interpretive consequences lead off such a meeting: from a misunderstanding of a Pauline passage (Rom 14:5-10) to the art of sacred Icons; and from the Trinitarian controversies of Byzantine church fathers to the medieval painter St.Andrej Rublëv and his most famous icon: “The Holy Trinity”. A work where—as Andrej Tarkovski has shewed in his celebrated movie of 1966—Abraham’s oak is a like a bell concealing the threefold person of God.